Pharmacokinetic Differences of the Glucuronide-Conjugated Metabolites of Magnoflorine, and Jatrorrhizine between Healthy Chinese and African Volunteers - ASSANHOU, Assogba Gabin (My University, 2015)
This short communication reports the pharmacokinetic differences of the glucuronide-conjugated metabolites of magnoflorine and jatrorrhizine between Chinese and African male volunteers. From an earlier report, glucuronidation was determined to be one of the main metabolic pathways and these two compounds were reported to differ significantly between the two races. Pharmacokinetic parameters of half-life,t1/2, time to reach maximum concentration, Tmax, maximum plasma concentration, Cmax, volume of distribution, Vd, area under the concentration-time curve, AUC and clearance, CL were considered. Statistically significant differences were observed in almost all the parameters studied in terms of their glucuronide-conjugated metabolites. The findings indicate the differences in hepatic metabolism of these two compounds between the two races.
Keywords: conjugate; glucuronide; metabolite; pharmacokinetics; races.